2005
DOI: 10.1177/1043659604273553
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Illness and Hmong Shamans

Abstract: Among the challenges health care personnel in California's central valley face has been finding ways to help Hmong Americans manage chronic illness. Interviews were conducted with 11 Hmong shamans diagnosed with diabetes or hypertension and were qualitatively analyzed to ascertain respondents' understanding and management of their illnesses. Hmong shamans are influential individuals within their communities and are often the resource persons to whom patients turn for information on health. Understanding the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…Directions were described as “indirect or hard to follow” (Horowitz et al, 2004, p. 639); some participants expressed the belief that doctors would prefer to prescribe medications because they were not trained to teach about diet. While the Hmong shaman in Helsel et al’s (2005) study did not specifically criticize healthcare provider teaching, one told of being taught to eat fish at every meal and another of being taught to eat three turkey sandwiches each day. One might question how effective the communication had been; both language and cultural barriers may have played a role.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Directions were described as “indirect or hard to follow” (Horowitz et al, 2004, p. 639); some participants expressed the belief that doctors would prefer to prescribe medications because they were not trained to teach about diet. While the Hmong shaman in Helsel et al’s (2005) study did not specifically criticize healthcare provider teaching, one told of being taught to eat fish at every meal and another of being taught to eat three turkey sandwiches each day. One might question how effective the communication had been; both language and cultural barriers may have played a role.…”
Section: Resultsmentioning
confidence: 99%
“…It was implied in Ogedegbe, Harrison, et al’s (2004) study that found people questioned the accuracy of the diagnosis if they did not have a family history of high blood pressure. Other less frequently mentioned etiologies included evil spirits (Wilson et al) and seasonal changes or pollen (Helsel et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations